2022
DOI: 10.3389/fpsyg.2022.865246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of News Overload on Social Media News Curation: Mediating Role of News Avoidance

Abstract: In this global village, easy access to news has resulted in many changes in the preferences and patterns of people for accessing news. Therefore, the present study has attempted to investigate the effects of news relevance, perceived quality, and news overloading on people’s news curation preferences. This study has also examined the mediating role of news avoidance between the news relevance, perceived quality, and news overloading on the news curation. A quantitative technique has been employed to check the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…A comprehensive comprehension of the role played by these affirmative psychological traits and experiences in students’ educational accomplishment empowers educators to formulate strategies that foster the cultivation of these vital proficiencies [ 92 , 93 ]. Propagating optimistic academic attitudes and behaviors, such as resilience, self-efficacy, and positive emotions, emerges as a viable strategy for augmenting students’ academic performance and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive comprehension of the role played by these affirmative psychological traits and experiences in students’ educational accomplishment empowers educators to formulate strategies that foster the cultivation of these vital proficiencies [ 92 , 93 ]. Propagating optimistic academic attitudes and behaviors, such as resilience, self-efficacy, and positive emotions, emerges as a viable strategy for augmenting students’ academic performance and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of news outlets in the digital environment increases, users have been exposed to an excessive amount of news. In this circumstance, information overload has been considered another significant problem for users (Zhang et al 2022). ANRS can predict news articles which users might be interested in and make personalized news recommendations for individual users.…”
Section: Introductionmentioning
confidence: 99%
“…ews avoidance is on the rise due to diminishing trust in news providers, political influence, and a surge in paywalls and subscription models (Newman et al, 2022). Existing studies have identified that intentional news avoidance, which refers to an individual's conscious decision to avoid news due to a dislike towards it, is driven by perceived news quality (Aharoni et al, 2021;Edgerly, 2021;Goyanes et al, (2023); Palmer and Toff, 2020;Skovsgaard and Andersen, 2020;Toff and Nielsen, 2018;Zhang et al, 2022).…”
mentioning
confidence: 99%